Tourist vacation preferences: the case of mass tourists to Crete. - Agiomirgianakis, George; Mihiotis, Athanasios; Andriotis, Konstantinos (My University, 2007)
Tourists during their vacations participate in a variety of activities. These activities range from active to passive ones and they may depend on various factors, including travel arrangement and sociodemographic characteristics. The aim of this article is to provide guidelines to Cretan destination managers for supplying well diversified tourist products that could satisfy particular requirements of tourists by examining tourist vacation preferences and identifying whether certain factors can influence tourists' preferences. The findings suggest that tourists visiting Crete prefer passive activities, and that the three main factors that influence tourists' activities are nationality, age, and season of visit. Despite the limitations of the study, it is evident that various policies are required by Cretan destination managers in order to provide activities directed to satisfy tourists' demand. These policies are discussed in relation to Crete's brand identity.
Keywords: Activities; Preferences; Mass; Alternative tourism; Policy-making; Crete